Prevalence, associated factors of nicotine dependence and disease severity in patients with schizophrenia / Nik Nasyrah Nek Mohamed - Nik Nasyrah , Nek Mohamed (2012)

(untitled)
Introduction: Studies have consistently shown that people with schizophrenia smoke at higher rates than the general population. Nicotine dependence, the commonest substance use disorder in patients with schizophrenia would increase the morbidity and mortality in this group of patients. To date, there have been no local data pertaining to smoking and nicotine dependence in patients with schizophrenia. Objective: This study aimed to determine the prevalence of smoking and nicotine dependence in a sample of outpatients with schizophrenia, factors associated with it and the severity of disease in the study sample. Methods: This was a cross-sectional study of 181 patients with a diagnosis of schizophrenia in the outpatient psychiatric clinic of a state hospital. Diagnosis was confirmed using the M.I.N.I. Patients who met the inclusion criteria was then assessed for the severity of disease using PANSS. Smokers were given the FTND to complete. All study participants were tested using a handheld device meant to measure carbon monoxide levels in the expired air. Results: The prevalence of smokers in was 38.1% and 73.9% of them were nicotinedependent. Being male (OR 62.36, p<0.01), Malay (OR 3.03, p<0.05), earning more than RM500 a month (OR 0.43, p<0.01) and concomitant drug and alcohol abuse (OR 12.96, p<0.01) was significantly associated with smoking but not to nicotine dependence. No association was found between FTND scores and PANSS scores. Conclusion: The prevalence of smoking and nicotine dependence in our study sample was very significant. It was found to be associated with higher monthly earnings. xviii Nicotine dependence should be included into the management of patients with schizophrenia. Specialized services are warranted to deal with this issue. Future local studies in this field are needed to address and identify other associated factors.